Pelatihan Simulasi Electronics Flight Instrument System Buatan Karya Anak Bangsa untuk Siswa SMK Negeri 12 Bandung - Ema Ema; Nina Hendrarini; Simon Siregar; Muhammad Ihsan Ismail (JITER-PM (Jurnal Inovasi Terapan - Pengabdian Masyarakat), 2023)
Presidential Instruction Number 9 of 2016 regarding the Revitalization of Vocational High Schools (SMK) emphasizes the importance of Vocational Education, which is education aimed at mastering practical skills in specific fields. Students are equipped with both theoretical knowledge and practical implementation. In order to develop vocational education in line with the competency needs of graduates (the "link and match" principle), the Ministry of Education and Culture (Kemendikbud) has made curriculum adjustments and developments. Previously, the curriculum was supply-driven, but it has now been transformed into a demand-driven approach to actively involve the business and industrial sectors (DUDI) in the vocational education process at SMKs. In line with this direction, we, from the Faculty of Applied Sciences, specifically the D3 Computer Technology program, in this period, will share our experiences through community engagement in the form of training in the Simulation of Electronics Flight Instrument Systems Made by Indonesian Youth. The objective of this training is to provide insights and enhance the competencies of SMK graduates in projects that can be implemented effectively.